Super-resolving normalising flows for lattice field theories - Bauer, Marc; Kapust, Renzo; Pawlowski, Jan M.; Temmen, Finn Leon (SciPost physics, 2025)
SciPost Journals Publication Detail SciPost Phys. 19, 077 (2025) Super-resolving normalising flows for lattice field theories